The Nurses' Experience Of Being A Nursepreneur In Independent Nursing Practice: Pengalaman Perawat Menjadi Nursepreneur dalam Praktik Keperawatan Mandiri - Yunita Fitri Rejeki; Andi Sudrajat; Fitra Herdian (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2023)
Nurses have the authority to open an independent nursing practice as one of the health services Nursepreneur is a business built based on the field of nursing the high number of nurses and the lack of independent nursing practice land into a phenomenon why nurses do not build a business in the field of nursing. Descriptive qualitative research method, sampling technique used purposive sampling and snowball sampling, with the number of informants three nurses who open nursing independent practice instrument used semi-structured interviews with data validity triangulation method and data analysis obtained five main themes. The results showed that the type of nursing independent practice established was wound care practice with a group wound care practice model, the strategic stage of establishing nursing independent practice by analyzing patient characteristics and analyzing the work environment and the regional environment, the obstacles are in the licensing flow in opening a nursing independent practice land that has not been structured and takes a long time and opportunities in mendiri nursing independent practice by branding between health agencies and through social media. Suggestions in this study need to develop quality standards for services to establish independent nursing practices and increase the involvement of professional organizations in fostering nurses who want to open independent nursing practices.